Natural Coinfection of Pseudomonas aeruginosa and Enteroaggregative Escherichia coli in a feral pigeon (Columba livia) - Vasconcelos, Ruben Horn; Bezerra, Windleyanne Gonçalves Amorim; Siqueira, Raul Antunes Silva; de Medeiros, Pedro Henrique Quintela Soares; Lucena, Ricardo Barbosa; Havt, Alexandre; da Silva, Isaac Neto Gomes; Maciel, William Cardoso (Acta Scientiae Veterinariae, 2017)
Background: Rock pigeon (Columba livia) is an exotic and invasive species of the Columbidae family found in several cities around the world, including Brazilian cities, and close to humans. This species is found in large populations often in public locations, where people may have contact. Several studies have demonstrated the isolation of human pathogens from these birds. However, there are scarce studies describing infections by Gram-negative bacteria to which pigeons are susceptible. Therefore, this report aimed to describe a case of natural coinfection of Pseudomonas aeruginosa and Enteroaggregative Escherichia coli in a feral pigeon. Case: A sick feral pigeon was delivered at the Laboratory of Ornithological Studies, State University of Ceará, Fortaleza, Brazil. Due to poor prognosis, the individual was euthanized with ketamine via intravenous injection and submitted to necropsy, in which samples were collected for microbiological and histopathological procedure. The procedure was performed aseptically and samples were collected from intestine, liver, spleen, heart and lung. Bacterial isolation was performed with culture media selective for Gram negative bacteria and strains were identified biochemically. Histopathological examination was performed with conventional method and slides were stained with hematoxylin and eosin. DNA from E. coli isolates was extracted with simples boiling method and submitted to uniplex conventional polymerase chain reaction (PCR) to diagnose diarrheagenic pathotypes with specific primers for the following genes: aaiC, aatA, eaeA, stx1, stx2, eltB, estA and ipaH. Escherichia coli was isolated from the intestine, liver, spleen and lung, while Pseudomonas aeruginosa was present in liver, spleen and lung. E. coli strains from liver and spleen were positive for the aaiC gene, which is a diagnostic gene for Enteroaggregative Escherichia coli (EAEC) pathotype. Necropsy revealed the presence of several caseous lesions around the head of the bird, cellulitis in the abdominal region, hepatomegaly, splenomegaly, hemorrhagic intestine and pericarditis. Microscopical findings were most intense in liver and lung samples, presenting vascular and inflammatory alterations. Histopathological alterations indicated an acute presentation of the infections and several lesions in different organs, demonstrating the septicemic characteristic of the microorganisms involved in this case. Discussion: Both pathogens in this report were identified mostly in the same organs, which may indicate that there was an association in the pathogenesis. However, the entry routes of infection in this case may have been different, considering that Pseudomonas aeruginosa was not isolated from the intestine. The histopathological findings were not pathognomonic for either pathogen. However, some characteristic lesions were observed, such as cellulitis, which is commonly attributed to Escherichia coli. EAEC strains are human pathogens that cause acute and persistent diarrhea around the world. These microorganisms could be potentially transmitted to humans, as suggested by other studies with feral pigeons and enteric pathogens. However, the absence of reports of pigeon-transmitted diarrheagenic infections in humans may suggest that pigeons are only reservoirs of these pathogens. In addition, as this report demonstrates, these birds may also suffer from these infections. In conclusion, the free-living pigeon presented a natural occurring case of coinfection by Pseudomonas aeruginosa and Enteroaggregative Escherichia coli. Both are human opportunistic pathogens, and may have public health implications